E-government in comoros : towards a transformational approach through the reengineering of public finance services and process - Abdou Mfoihaya, Said (2014)
The aim of this thesis is to investigate the current e-Government environment and make recommendations for possible solutions to the adoption and development of e-Government projects in Comoros. The field of e-Government is playing a prominent role on economic as well as social developments in developed and developing countries. Recent studies have shown that advanced countries in e-Government implementation achieved good status both in socio-economic and social aspects. There have been numerous models and frameworks developed for e-Government implementation programs in the literature. The study undertaken in this thesis is based on available models, frameworks, and current practices in different countries. That means, the nature of this study is on a case study research. The study started with a historical background of the e-Government progress across different horizons. It continues with the investigation on e-Government models, frameworks, and the experience of different countries in this field. Also the study examined several theoretical and operational frameworks in order to identify issues, aspects, and techniques that can support the development of e-Government. Then, later the study discussed on the current e-Government environment for the purpose of identifying the gaps existing between this environment and established e-Government programs. The findings obtained from the literature journey lead into the development of a hypothetical framework designed to address the gaps and satisfy the requirements for a successful application of e-Government services. Another result is the identification of key parameters (areas) where transformation does happen. These two results are supported by a case study model for the transformation of the Comoros public finance sector. The results obtained are evaluated against established frameworks available in the literature. During the evaluation process several recommendations have been given. This study achieved two prominent contributions. It can be used by Comoros Government policy makers to drive changes in the Comoros e-Government program. Also the study is useful for researchers for the development of further studies. Although the research questions have been answered, the study presents some limitations. It needs to be tested in the real world environment to confirm its strengths and identify drawbacks for further improvements.